Antimicrobial susceptibility of escherichia coli isolated from chicken meat - L. Kalaiselvi; P. Karthick Venkatesh; S. Ramesh; K.V. Venkateswaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted to evaluate the antimicrobial resistance in Escherichia coli strains isolated from chicken meat. One hundred and five chicken meat samples were collected from retail broiler outlets in Chennai, Tamil Nadu, India and processed for bacteria isolation. Thirty one E. coli strains were isolated and the isolated strains were tested for antimicrobial susceptibility. All isolates showed resistance to two or more antimicrobials. The isolates exhibited resistance to ampicillin (93.55%), ampicillin-sulbactam (67.74%), amoxicillin-clavulanate (100%), erythromycin (77.42%), tetracyclines (61.29%) and cotrimaxazole (64.52%). Multidrug resistance was observed in 29 (93.55%) isolates. The results highlight the prevalence of multidrug resistance E. coli strains which is a serious threat to public health. Hence, the surveillance system should be strengthened and antimicrobial drug usage in the poultry industry should be optimized to prevent emergence and spread of antimicrobial resistance.